ANALISIS HARAPAN DAN PENILAIAN KONSUMEN TERHADAP PENCITRAAN TOKO DALAM USAHA MENINGKATKAN KEPUASAN KONSUMEN DI TOKO HEAVENLY BLUSH PONDOK INDAH MALL JAKARTA SELATAN - Deliana Deliana; Dwi Gemina (Jurnal Visionida, 2016)
These purpose of the research are: 1) to know about the customers expectation and customers rating in the store image (including main products, promotion, comfortability, facilities, services, store ambience, and brand); 2) To know about the implementation of the strategy as effort to increase the customers’ satisfaction; 3) To know about the customer satisfaction to the store image (Including: main product, promotion, comfortability, facilities, services, store ambience, and brand). This research is conducted in Heavenly blush outlet Pondok Indah at South Jakarta. The descriptive method is used in this research. The purposive sampling is used for the sampling technique. Data are collected by questionnaire, observation, and interview. The Data Analyzed include validity test, reliability test, descriptive analysis test, Importance and Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The result of the research are: 1) The consumers thought that some attribute of store image are important, such as souvenirs, prize, degree of movement, new products, and catalogue in the proper position. But on the other hand, both of customer satisfaction and the customer expectation are still low. 2) the percentage of customers satisfaction index is 65% which shows that the costumer,s appraise to the quality of store imagein Heavenly Blush is in average.Keyword : store imaging, customer expectation, customer satisfaction